(untitled) (Pulse, 2015)
Uterine artery pseudoaneurysm (UAP) occurs rarely and can develop after various gynecologic or obstetric procedures. The delayed diagnosis of this disease often results in life-threatening hemorrhage. Here is described a case of UAP after cesarean section. The patient visited gynecology outpatient department of AHD 60 days after cesarean section done outside AHD because of abnormal per vaginal bleeding. After her cesarean section she had undergone laparotomy outside AHD for post partum haemorrhage but those papers were not available. From there she was sent to our radiology department for color Doppler TVS examination and here she was diagnosed as a case of UAP using color Doppler ultrasonography. The most frequent cause of UAP is cesarean section, which accounted for 47.4% of all cases. Previous studies show that the definitive diagnosis was made at angiography (41.2%), computed tomography (29.4%), or color doppler ultrasonography (29.4%). Almost all cases (94.1%) were conservatively treated with transcatheter uterine artery embolization. Consideration of UAP in the differential diagnosis is crucial for proper treatment before rupture and to preserve fertility. Pulse Vol.7 January-December 2014 p.56-60